A Natural History of the Emirates - Burt, John A. (Springer Nature, 2024)
For many people, thoughts of the United Arab Emirates conjure images of ultramodern skyscrapers and rolling sand dunes. However, the Emirates are a rich mosaic of ecosystems and habitats that support surprisingly diverse communities of organisms, and there is growing awareness of the importance of these previously underappreciated natural assets. A Natural History of the Emirates provides a comprehensive overview of the unusual environmental setting of this young nation, and surveys the major ecosystems and the marine and terrestrial organisms occurring across the nation. From freshwater streams in the hyperarid Hajar Mountains to the world's most temperature-tolerant coral reefs, the UAE is home to an astounding variety of uniquely adapted organisms that are providing insights into climate change and how organisms cope with and respond to extreme environmental conditions. The book closes with a section on human interactions with this unique environment, and proposes initiatives to ensure the protection of these unique natural assets into the future. This is an open access book.